Pengaruh Ukuran Perusahaan Dan Corporate Governance Terhadap Manajemen Laba Di Industri Perbankan Indonesia: Studi Kasus Pada Industri Perbankan Yang Terdaftar Di BEI Pada Tahun 2016-2018 - Karina Karina; Sutarti Sutarti (Institut Bisnis dan Informatika Kesatuan, 2021)
The purpose of this research is to provide empirical evidence of the affect of ownership concetration, firms size, and corporate governance mechanisms on earnings management. Ownership concetration was measure by the biggest stock of individual or organization, firms size was measure by natural logaritma of net assets, and corporate governance mechanisms were measure by three variabels (composition of board of commisioner, audit quality were measure by industry specialize audit firm, and composition of audit committee). Earnings management was measure by discretionary accruals use Modified Jones Method. The population of this research is 41 companies in the banking sector which were listed in Indonesian Stock Exchange (IDX). The research data were collected from banking companies financial statement for the period of 2016 to 2018. Based on purposive sampling method. The reseacrh hypotesis were tested using multiple regression analysis. The results of this research show that firm size, firm of commissioner and proportion of commissioner have significant relationships with earnings management. Next, variables composition of board of commissioner, ownership concetration and specialize audit firm have no significant relationship with earnings management. Keywords: ownership concetration, firms size, corporate governance, earnings management